Contact dependent reproducible hypomania induced by deep brain stimulation in Parkinson's disease: clinical, anatomical and functional imaging study - Ulla, Miguel; Thobois, Stéphane; Llorca, Pierre-Michel; Derost, Philippe; Lemaire, Jean-Jacques; Chereau-Boudet, Isabelle; de Chazeron, Ingrid; Schmitt, Audrey; Ballanger, Bénédicte; Broussolle, Emmanuel; Durif, Franck (Journal of neurology, neurosurgery and psychiatry, 2011)
Hypomanic symptoms depending on anatomical location of contacts are reported in patients with Parkinson's disease (PD) treated by deep brain stimulation (DBS) of the subthalamic nucleus (STN). However, the underlying cortical and subcortical dysfunction is debated. In this study, five PD patients implanted with DBS–STN who presented with reversible and reproducible hypomanic symptoms after stimulation of specific ‘manic’ contacts were investigated. Hypomanic symptoms were assessed using the Bech and Rafaelsen Mania Scale (MAS). Three dimensional anatomical location of ‘euthymic’ and ‘manic’ contacts, after matching the postoperative CT scan with the preoperative stereotactic MRI, and a H215O positron emission tomography (PET) study testing ‘euthymic’ and ‘manic’ contacts, were performed. Under ‘euthymic’ conditions, MAS score (mean±SD) was 0.6±0.5 compared with 7.8±3.1 under ‘manic’ conditions. Nine of 10 ‘manic’ contacts were located in the substantia nigra, mainly in its ventral part. PET showed that hypomania was associated with strong asymmetrical cerebral activation involving preferentially the right hemisphere and was mediated by activation of the anterior cingulate and medial prefrontal cortex. The present study demonstrates the role of the subcortical structures in the genesis of hypomania in PD patients treated with DBS and stresses the involvement of the substantia nigra.